The risk of endocrine immune-related adverse events induced by PD-1 inhibitors in cancer patients: a systematic review and meta-analysis - Zhao, Pengfei; Zhao, Ting; Yu, Lihong; Ma, Wenming; Liu, Wenyu; Zhang, Chenning (Frontiers in Oncology, 2024)
Objective: Endocrinopathies are the most common immune-related adverse events (irAEs) observed during therapy with PD-1 inhibitors. In this study, we conducted a comprehensive systematic review and meta-analysis to evaluate the risk of immune-related endocrinopathies in patients treated with PD-1 inhibitors. Methods: We performed a systematic search in the PubMed, Embase, and Cochrane Library databases to retrieve all randomized controlled trials (RCTs) involving PD-1 inhibitors, spanning from their inception to November 24, 2023. The comparative analysis encompassed patients undergoing chemotherapy, targeted therapy, or receiving placebo as control treatments. This study protocol has been registered with PROSPERO (CRD42023488303). Results: A total of 48 clinical trials comprising 24,514 patients were included. Compared with control groups, patients treated with PD-1 inhibitors showed an increased risk of immune-related adverse events, including hypothyroidism, hyperthyroidism, hypophysitis, thyroiditis, diabetes mellitus, and adrenal insufficiency. Pembrolizumab was associated with an increased risk of all aforementioned endocrinopathies (hypothyroidism: RR=4.76, 95%CI: 3.55-6.39; hyperthyroidism: RR=9.69, 95%CI: 6.95-13.52; hypophysitis: RR=5.47, 95%CI: 2.73-10.97; thyroiditis: RR=5.95, 95%CI: 3.02-11.72; diabetes mellitus: RR=3.60, 95%CI: 1.65-7.88; adrenal insufficiency: RR=4.80, 95%CI: 2.60-8.88). Nivolumab was associated with an increased risk of hypothyroidism (RR=7.67, 95%CI: 5.00-11.75) and hyperthyroidism (RR=9.22, 95%CI: 4.71-18.04). Tislelizumab and sintilimab were associated with an increased risk of hypothyroidism (RR=19.07, 95%CI: 5.46-66.69 for tislelizumab and RR=18.36, 95%CI: 3.58-94.21 for sintilimab). For different tumor types, both hypothyroidism and hyperthyroidism were at high risks. Besides, patients with non-small cell lung cancer were at a higher risk of thyroiditis and adrenal insufficiency. Patients with melanoma were at a higher risk of hypophysitis and diabetes mellitus. Both low- and high-dose group increased risks of hypothyroidism and hyperthyroidism. Conclusions: Risk of endocrine irAEs may vary in different PD-1 inhibitors and different tumor types. Increased awareness and understanding of the risk features of endocrine irAEs associated with PD-1 inhibitors is critical for clinicians.